2021
DOI: 10.1097/coh.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in HIV infection

Abstract: Purpose of review The exosomes play a critical role in HIV infection, which constitute a pathway to release intracellular material and exchange material and information between cells. Exosomes have become a hotspot in the field of AIDS research. This review introduces the formation process of HIV particles and exosomes, and summarizes the role of exosomes in the progression of HIV disease from multiple aspects. Recent findings Many components of the exosomes involved in HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 102 publications
(116 reference statements)
0
21
0
1
Order By: Relevance
“…Taken together, these results imply that plasma EV-derived monocytes may inform cardiovascular risk through inflammation and immune activation among individuals on cART with viral suppression. The pathophysiological mechanism underlying this relationship remains undefined, though candidate mechanisms include EV-associated cytokines ( 33 ), viral proteins, microRNA (miRNA), bioactive lipids, or other EV cargo (reviewed in reference 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results imply that plasma EV-derived monocytes may inform cardiovascular risk through inflammation and immune activation among individuals on cART with viral suppression. The pathophysiological mechanism underlying this relationship remains undefined, though candidate mechanisms include EV-associated cytokines ( 33 ), viral proteins, microRNA (miRNA), bioactive lipids, or other EV cargo (reviewed in reference 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes isolated from patients with infectious diseases such as tuberculosis and HIV/AIDS reflect the disease state in the body. [ 195 , 196 ] Exosome isolation techniques and challenges have been outlined below for HIV/AIDS. Nef proteins secreted by exosomes derived from HIV‐infected cells trigger T‐cell death and promote disease progression, making exosome isolation a valuable tool in determining HIV patient prognosis.…”
Section: Exosome Processing and Isolationmentioning
confidence: 99%
“…At present, exosomes have been found to be mainly generated by mechanisms dependent on or independent of endosomal sorting complex required for transport (ESCRT).ESCRT consists of different protein complexes and helper proteins, which participate in the formation of membrane-invagination and polyvesicle body (MVBs), and mediates the fusion of MVBs with cell membrane, resulting in the formation of exosomes. Meanwhile, IT has been found that MVBs can also be produced in a mechanism independent of ESCRT, enriching the research on exosome formation [ 5 ].…”
Section: Exosome Formation and The Biogenetic And Sorting Mechanisms Of Exosomal Mirnasmentioning
confidence: 99%